From Mating to Milk Access: A Review of Reproductive Vocal Communication in Mice - Capas-Peneda, Sara; Saavedra Torres, Yolanda; Prins, Jan-Bas; Olsson, I. Anna S. (Frontiers in Behavioral Neuroscience, 2022)
Vocalizations play a central role in rodent communication, especially in reproduction related behaviours. In adult mice (Mus musculus) the emission of ultrasonic vocalizations (USVs) has been observed in courtship and mating behaviour, especially by males. These have been found to have distinctive individual signatures that influence female choice of mating partner. The most recent findings show that vocal communication also has a role in parental cooperation, in that female mice communicate with male partners in ultrasonic frequencies to induce paternal behaviour. Infant vocalizations form the other important part of reproductive vocal communication. Although born deaf, neonatal mice are capable of producing vocalizations since birth. As an altricial species, successful mother-infant communication is essential for survival, and these vocalizations are important modulators of maternal behaviour. Three main types of infant vocalizations have been identified and characterized. Most research has addressed pure USVs, related to stressful situations (e.g. cold, isolation, handling, presence of unfamiliar males or predators), which usually elicit maternal search and retrieval. In addition, broad-band spectrum signals, emitted post-partum during cleaning of foetal membranes, inhibit biting and injury by adults and “wriggling calls”, emitted during suckling, release maternal behaviour (such as licking). Several variables have been identified to modulate vocalizations in mice, including individual characteristics such as strain/genotype, age, sex and experimental factors such as pharmacological compounds and social context. In recent years, there has been a big increase in the knowledge about the characteristics of vocal communication in rodents due to recent technological advances as well as a growing interest from the neuroscience community. Vocalization analysis has become an essential tool for phenotyping and evaluating emotional states. In this review, we will (i) provide a comprehensive summary of the current knowledge on mouse reproductive vocal communication and (ii) discuss the most recent findings in order to provide a broad overview on this topic.